Cocoa rehabilitation and establishment in cocoa-based farming systems in the humid forest zones of west Africa - Asare, R.; Kofituo, R.K. (2022)
The cocoa rehabilitation and establishment in cocoa-based farming systems in the humid forest zones of West Africa is part of the larger TAFS-WCA initiative that seeks to enhance access to quality, nutrient-dense seed, and climate-smart good agricultural practices (GAP) and reduced post-harvest losses and to see how these have a positive impact on food and nutrition and health security. Within the cocoa sector in West Africa, this initiative seeks to improve yields of cocoa and food crops and enhance the efficient growth of timber tree species to reduce the impact of cocoa production on forest and biodiversity. The reconnaissance survey seeks to establish the current condition within the cocoa system in relation to the potential for rehabilitation of cocoa farms starting from the Ashanti and Ahafo regions of Ghana. Existing IITA partners in the cocoa sector in Ghana including Ofi, Cargill, Mondelez International, Barry Callebaut, Kuapa Kokoo and Rockwinds were engaged in this survey. Preliminary findings show that majority of farmers interviewed within the study areas have aged and diseased cocoa farms and are frustrated on rehabilitation due to two reasons: i) past failed attempts by similar initiatives and ii) the fear of losing income when cocoa farms are rehabilitated as cocoa economy is their mainstay. Most cocoa farmers have shade trees on their farms, but the required quantity and quality needed for compatibility leaves much to be desired in the given agroecological zone. There is food sufficiency among the cocoa farmers and most have dedicated land for food crop cultivation. There were identified forests in the study area. Farmers with fallow lands seek to expand their cocoa farms and use part for food crop cultivation. There is the need for farmers to rehabilitate their cocoa farms within the study area based on a preferred model that will ensure establishment of the farm and early income for farmers to encourage and promote a large scale rehabilitation process in the cocoa landscape. This will help to discourage extensification and promote intensification.